The Urgence of Renewal Investment Law and Investment Dispute Settlement in Indonesia - Tubagus Andri Purnama; Yohanes Firmansyah; Anna Maria Tri Anggraini‬; Elfrida Ratnawati Gultom; Imam Hartanto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2022)
Legal certainty can be reached by good and explicit principles in a legislation, as well as its application. Investment requires legal certainty as well. On April 26, 2007, the Investment Law No. 25 of 2007 was enacted. This legislation was enacted to replace Law No. 1 of 1967 on Foreign Investment and Law No. 6 of 1968 on Domestic Investment. There are eleven factors that serve as benchmarks for gauging a country's ease of doing business. One of the indications is related to the resolution of investment conflicts, or in this case, contract enforcement and bankruptcy proceedings. According to the Doing Business 2019 report, Indonesia ranks 73rd (seventy-three) in terms of ease of doing business. Indonesia's EoDB ranking remains distant from the aim of entering the world's top 40 (forty) ranks. This is due to the fact that, among other things, dispute resolution in Indonesia still has various issues, including basic regulations, the trial procedure, and decision implementation. Meanwhile, affordable, fast, and simple conflict resolution facilities are required in the corporate world (according to EoDB indications). The results of this descriptive analytical research utilizing a normative juridical approach reveal that there is no implementing regulation of Law Number 25 of 2007 concerning Investment, which focuses on discussing investment disputes, therefore there is no strong legal certainty in investing in Indonesia. Furthermore, there are several issues concerning the resolution of bankruptcy cases, some of which stem from regulations, namely Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, some of which can result in certain interests, the length of the bankruptcy court process, and legal certainty following the bankruptcy decision. A breakthrough or update that can support EoDB is required, one of which can be done in the field of investment dispute resolution, particularly connected to contract enforcement and bankruptcy case settlement, by creating implementing regulations and updating associated regulations.